Observations of postglacial sea‐level rise in northwest European traditions. Issue 4 (16th December 2021) - Nunn, Patrick D.; Creach, Axel; Gehrels, W. Roland; Bradley, Sarah L.; Armit, Ian; Stéphan, Pierre; Sturt, Fraser; Baltzer, Agnès
Abstract: In preliterate contexts, diverse knowledge was accumulated, processed and communicated orally. Recent research demonstrates that observations of memorable events were transferred in this way for thousands of years sometimes. Much of this information was eventually written down to reach literate audiences, which commonly judge such 'myths and legends' to be cultural inventions rather than ancient memories. This study examines 15 'submergence stories' from northwest European coasts and argues that they plausibly represent memories of postglacial sea‐level rise, which, in this region, was spatially and temporally variable owing to the interaction of sea‐level rise with glacial isostatic adjustment. This study combines culture history and knowledge of earth rheology to argue that memories of the effects of postglacial land submergence in northwest Europe have endured for 5000–15, 000 years. This requires a longevity of memory, orally communicated, that is not unprecedented, yet surprises many. It also shows that scientists might benefit from trying to better understand oral traditions from cultures elsewhere in the world that may have preserved observations of memorable events.